Assessment of the carbon emissions reduction potential of China's iron and steel industry based on a simulation analysis. (15th September 2019) - Li, Zhaoling; Dai, Hancheng; Song, Junnian; Sun, Lu; Geng, Yong; Lu, Keyu; Hanaoka, Tatsuya
Abstract: This study provides a feasible approach for decreasing the carbon emissions of China's iron and steel industry (ISI) by 2030 using the environmental-economic simulation model. The ISI and its upstream industries are optimized by introducing both technological upgrades and environmental policies. Six scenarios are designed, including business-as-usual ( BaU ), industrial upgrades ( tec ), carbon tax ( tax ), carbon trading ( tra ), and combination ( cob ) 1 and cob2, which combine the tec, tax and tra scenarios. The results show that the tec scenario can effectively curb carbon emissions. The tax scenario significantly promotes low emissions technologies. The cob2 scenario has the most stringent carbon emissions control effect and helps the ISI meet the Intended Nationally Determined Contributions (INDCs) target of China. Moreover, the rates of carbon emissions increase under the tec, cob1, and cob2 scenarios will decrease after 2027, indicating that it is highly possible that carbon emissions will peak in 2030. The decrease in crude steel production and electricity demand is also essential for the carbon emissions reduction of the ISI. This research comprehensively analyzes the factors influencing carbon emissions from the Chinese ISI. Analyzing this issue from the industrial chain perspective provides a new research scope for future simulation model studies.